2016
DOI: 10.1289/ehp204
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization Level and Vulnerability to Heat-Related Mortality in Jiangsu Province, China

Abstract: Background:Although adverse effects of high temperature on mortality have been studied extensively in urban areas, little is known of the heat–mortality associations outside of cities.Objective:We investigated whether heat–mortality associations differed between urban and nonurban areas and how urbanicity affected the vulnerability to heat-related mortality.Methods:We first analyzed heat-related mortality risk in each of 102 counties in Jiangsu Province, China, during 2009–2013 using a distributed-lag nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 38 publications
5
58
0
Order By: Relevance
“…Our study showed stronger heat effects in rural counties than in urban counties, which was in line with a previous study39. Moreover, a recent provincial investigation conducted in Jiangsu, China found that, less urban counties showed a higher pooled heat-related mortality risk with 1.43 (95% Posterior Intervals: 1.36–1.50) compared with 1.26 (1.23–1.30) in more urban counties33. These inconsistent results highlight a need to comprehensively understand the contributing proportion attributable to those independent factors influencing heat-related mortality, in order to design county-targeted preventive and control strategies.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed stronger heat effects in rural counties than in urban counties, which was in line with a previous study39. Moreover, a recent provincial investigation conducted in Jiangsu, China found that, less urban counties showed a higher pooled heat-related mortality risk with 1.43 (95% Posterior Intervals: 1.36–1.50) compared with 1.26 (1.23–1.30) in more urban counties33. These inconsistent results highlight a need to comprehensively understand the contributing proportion attributable to those independent factors influencing heat-related mortality, in order to design county-targeted preventive and control strategies.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it is less prone to measurement error [37]. Interestingly, other studies [20,47] reported similar results regardless of the temperature metric used.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, many of these studies have focused on urban areas due to the urban heat island effect and high density of susceptible population (Huang et al, 2011; Li et al, 2013). However, there is emerging evidence supporting high risk of heat-related health impacts in nonurban areas (Bennett et al, 2014; Chen et al, 2016; Madrigano et al, 2015; Sarofim et al, 2016; Sheridan and Dolney, 2003). Less is known about how total and cause-specific mortality will change in response to changes in projected heat exposure in nonurban areas.…”
Section: Introductionmentioning
confidence: 99%
“…We applied urban-specific and nonurban-specific ERFs for heat-related total, cardiovascular (including more specific causes of stroke and ischemic heart disease (IHD)), and respiratory (including chronic obstructive pulmonary disease (COPD)) mortality from our previous analysis (Chen et al, 2016) to multiple climate and population projections to estimate the climate change-induced heat-related health burdens in 104 counties of Jiangsu Province, China.…”
Section: Introductionmentioning
confidence: 99%